PERBEDAAN QIR’AH MUTAWATIRAH DAN IMPLIKASINYA DALAM PENETAPAN HUKUM - Nur Rohmah Zamamah; Muhammad Shohib (MIYAH : Jurnal Studi Islam, 2020)
Abstrak: Qira’ah is the difference in the reading of the Qur’an terms of pronunciation and other methods which are inherently continuous to the prophet. Qira’ah has two versions relating to the dialect of language (lahjah) and the substance of lafadz, if qira’ah is related to lahjah then it does not have implications for interpretation, such as reading isymam which has a difference between writing and reading. And if qira’ah is related to the substance of lafadz then it has implications for interpretation. Specifically, this paper contributes to the existence of the differences of qira’ah mutawatirah and has implications for legal stipulation. By using the tahlili interpretation method which has a very broad scope. The results of the study of the verses that has differences in qira’ah mutawatirah and has implications for the stipulation of law in the al-Qur’an are six verses, namely al-Baqarah verse 222, al-Nisa>’ verse 43, al-Ma>idah verse 6, al-Baqarah verse 125, al-Baqarah verse 229 and al-Maidah verse 95.Keywords: Difference of qira’ah, Implications, Stipulation of Law.